Studying the Flux Density of Bright Active Galaxies at Different Spectral Bands (Baghdad Science Journal, 2019)
Statistical studies are reported in this article for an active galactic nuclei sample of different type of active galaxies Seyferts 1, Seyferts 2, and Quasars. These sources have been selected from a Catalogue for bright X-ray galaxies. The name of this index is ROSAT Bright Source Catalogue (RBSC) and the NRAO VLA Sky Survey (NVSS). In this research, multi-wavelength observational bands Radio at 1.4 GHz, Optical at 4400 A0, and X-ray at energy 0.1-2.4 KeV have been adopted in this study. The behavior of flux density ratios has been studied , with respect to the absolute magnitude . Furthermore, the Seyfert1 and Seyfert 2 objects are combined in one group and the QSOs are collectest in another group. Also, it has been found that the ratios , are increasing towards fainter optical absolute magnitude especially in Quasars.